Investigation of the optical properties of CuIn (Se, S)2 thin films for photovoltaic application. (2019) - Bouich, A.; Hartiti, B.; Ullah, S.; Ebn Touhami, M.; Mari, B.; Santos, D.M.F.
Abstract: In this study, thin CuInSe2 and CuInS2 ternary films were successfully deposited on Indium ThinOxide (ITO) substrates by a low-cost electrochemical deposition technique.During the deposition of thin layers, the pH of the solution was maintained at 1.6, the applied potential at -0.750 V and the deposition time at 60 minutes, to control the ionic concentration of the solution; Sodium citrate has been used as a complexing agent.The morphology of the films was examined by optical microscopy, a homogeneous and without pin hole films were founded based on sulfur compared to those prepared with selenium precursor.Optical parameters such as absorbance (A), transmittance (T), band gap energy (Eg) and optical constants like refractive index (n), extinction coefficient (k) and dielectric constant (ε) were extracted using UV-Vis spectroscopy.It is remarkable that all films have a high absorption capacity and low transmittance. But there is a small difference in the results in terms of percentage (%) of the absorbance and transmittance of the films. The highest transmittance value is observed for selenium (12%) with band gap energy about 1.52 eV and for the deposited film with sulfur the lower transparency of 9% at 800 nm with band gap energy about 1.46 eV.The higher value of the refractive index (3.5) for films prepared using sulfur as a precursor is attributed to the thickness (1.99 μm) of the films andthe important value of the extinction coefficient (0.055) is observed for this precursor because of the strong absorption of this film.